Pivoting from ‘Responsible Populism’ to Reactionary Conservatism: The Case of the Perussuomalaiset - Thatcher, Iris (Scandinavian-Canadian Studies / Études scandinaves au Canada)

(untitled) (Association for the Advancement of Scandinavian Studies in Canada, 2022)
Although the Perussuomalaiset (True Finns or Finns Party) has its roots in populism under Timo Soini, this article argues that the party has transitioned to reactionary conservatism under Jussi Halla-aho. This change in leadership displayed a shift in party ideology: one that used to be more focused on the Eurosceptic economic narrative to one fixated on multiculturalism and anti-immigration. The shift in ideology and party rhetoric can be traced from party documents, use of blogging from both Soini and Halla-aho, and growing electorate support for the Perussuomalaiset during the 2010s. The article concludes with a discussion of how reactionary conservatism could be applied to other far right-wing parties in the Nordic region, while highlighting that the rise of reactionary conservate parties can pose notable challenges to democratic norms and political stability.